High Energy Exoplanet Transits. Issue Volume 12:Issue S328(2016) (12th September 2017) - Llama, Joe; Shkolnik, Evgenya L.
Abstract: X-ray and ultraviolet transits of exoplanets allow us to probe the atmospheres of these worlds. High energy transits have been shown to be deeper but also more variable than in the optical. By simulating exoplanet transits using high-energy observations of the Sun, we can test the limits of our ability to accurately measure the properties of these planets in the presence of stellar activity. We use both disk-resolved images of the Solar disk spanning soft X-rays, the ultraviolet, and the optical and also disk-integrated Sun-as-a-star observations of the Lyα irradiance to simulate transits over a wide wavelength range. We find that for stars with activity levels similar to the Sun, the planet-to-star radius ratio can be overestimated by up to 50% if the planet occults an active region at high energies. We also compare our simulations to high energy transits of WASP-12b, HD 189733, 55 Cnc b, and GJ 436b.